Protective Effects of N1-Methylnicotinamide Against High-Fat Diet- and Age-Induced Hearing Loss via Moderate Overexpression of Sirtuin 1 Protein - Miwa, Toru (Frontiers in Cellular Neuroscience, 2021)
Age-related hearing loss (ARHL) is the most common form of hearing loss and the predominant neurodegenerative disease associated with aging. Sirt1 is associated with the most complex physiological processes, including metabolism, cancer onset, and aging. Sirtuin 1 (SIRT1) protein levels are enhanced by the conversion of nicotinamide to N1-methylnicotinamide (MNAM), independent of its mRNA levels. Moreover, MNAM has implications in increased longevity achieved through its mitohormetic effects. Nicotinamide N-methyltransferase (Nnmt) is an enzyme involved in MNAM metabolism, and its level increases under caloric restriction (CR) conditions. The CR condition has implications in delaying ARHL onset. In this study, we aimed to determine the relationship between diet, hearing function, SIRT1 and SIRT3 expression levels in the inner ear, and cochlear morphology. Mice fed with a high-fat diet (HFD), HFD + 1% MNAM, and low-fat diet were monitored for age-related auditory-evoked brainstem responses, and changes in cochlear histology, metabolism, and protein and mRNA expressions were analyzed. Our results revealed that the HFD- and aging-mediated downregulated expression of SIRT1 and SIRT3 promoted hearing loss that was obfuscated by MNAM supplementation-induced upregulated expression of cochlear SIRT1 and SIRT3. Thus, our results suggest that MNAM can be used as a therapeutic agent for preventing ARHL.